STRATEGI PEMBELAJARAN ATM UNTUK MENINGKATKAN HASIL BELAJAR MENULIS TEKS BERITA SISWA - Riyanti, Asih; Anita Safitri; Resda Yanti; Setyo Ayu Giri Andini; Tasya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the application of ATM (Observe, Imitate, Modify) learning strategies in improving the learning outcomes of writing news texts for grade VII students at SMP Negeri 11 Tarakan. The research used a qualitative descriptive method with data sources in the form of Indonesian language teachers and grade VII students. Data collection techniques are carried out through observation, interviews, and documentation of student writings. The ATM strategy is implemented through three stages, namely observing news text examples, imitating the structure and pattern of writing, and modifying the writing according to students' ideas and creativity. The results of the study show that the ATM strategy is able to help students understand the structure, elements, and linguistic rules of news texts more easily and gradually. The use of learning media in the form of printouts also supports students in developing ideas and compiling writing systematically. In addition, teachers play an active role in creating a comfortable learning atmosphere, providing motivation, and guiding students during the learning process. The learning outcomes of students showed that most of them had reached the Minimum Completeness Criteria (KKM) with scores in the good category. However, there are still obstacles in the form of students' dependence on the examples given. Therefore, it is necessary to develop more varied learning strategies so that students' creativity and independent thinking skills can increase optimally. Keywords: ATM strategy, writing learning, news text, learning outcomes, grade VII students, Bahasa Indonesia.